2020
DOI: 10.14505//jemt.v11.5(45).09
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Competitiveness of the National Economy by Inhancing Energy Efficiency and Diversifying Energy Supply Sources in Rural Areas

Abstract: The idea of inhancing competitiveness of the national economy was developed in the article from the position of improving energy efficiency and diversifying energy supply sources in rural areas, considering promising directions of development. Current situation in the country was analyzed, and comparisons with European countries were made, promising ways of sustainable rural development were determined, connected with the creation and improvement of the existing tools for using renewable energy sources. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The leapfrogging hypothesis, however, challenges this status quo by postulating that low-income countries can expand their economies with modern low-carbon technologies without relying on conventional or fossil fuels as the advanced countries did (Gallagher 2006). This concept is based on the premise that modern and cleaner energy technologies can be transferred to, and widely deployed in developing countries.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The leapfrogging hypothesis, however, challenges this status quo by postulating that low-income countries can expand their economies with modern low-carbon technologies without relying on conventional or fossil fuels as the advanced countries did (Gallagher 2006). This concept is based on the premise that modern and cleaner energy technologies can be transferred to, and widely deployed in developing countries.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This concept is based on the premise that modern and cleaner energy technologies can be transferred to, and widely deployed in developing countries. Gallagher (2006) contends that such technology transfer may not be practical, especially where the recipient developing countries lack the technological capabilities to develop or integrate/localize these technologies from the advanced countries.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The use of correlation analysis in the study made it possible to determine the degree of influence of the level of provision of agro-industrial enterprises with RES on their competitiveness (Gorb et al 2020). It was found that there is a steady relationship between the introduction of RES in the activities of companies, the level of their competitiveness, and energy conservation costs.…”
Section: Discussionmentioning
confidence: 99%
“…Koszt energii, traktowany wprost, jest czynnikiem decydującym o międzynarodowej konkurencyjności branż produkujących na eksport [McKinsey, 2009;APEC, 2016], podobnie zresztą jak jej pośrednie formy, np. efektywność energetyczna [Głowacka, 1996, s. 29-30;Gorb i in., 2020Gorb i in., , s. 1114Gorb i in., -1123.…”
Section: Podsumowanieunclassified